The Functionalization of a Honeycomb Polystyrene Pattern by Excimer Treatment in Liquid - Slepička, Petr; Siegel, Jakub; Šlouf, Miroslav; Fajstavr, Dominik; Fajstavrová, Klára; Kolská, Zdeňka; Švorčík, Václav (Polymers, 2022)
In this article, we present a unique combination of techniques focusing on the immobilization of noble metal nanoparticles into a honeycomb polystyrene pattern prepared with the improved phase-separation technique. The procedure consists of two main steps: the preparation of the honeycomb pattern (HCP) on a perfluoroethylenepropylene substrate (FEP), followed by an immobilization procedure realized by the honeycomb pattern's exposure to an excimer laser in a noble metal nanoparticle solution. The surface physico-chemical properties, mainly the surface morphology and chemistry, are characterized in detail in the study. The two-step procedure represents the unique architecture of the surface immobilization process, which reveals a wide range of potential applications, mainly in tissue engineering, but also as substrates for analytical use.
Keywords: nanostructure; honeycomb; excimer laser; gold nanocluster; immobilization; polystyrene; morphology